KEJADIAN STUNTING: ASI EKSKLUSIF DAN KETERSEDIAAN AIR BERSIH - Sriyanah, Nour; Yulita, Hendra; Safitry, Rusni; Assagaff, Farha (Ensiklopedia of Journal, 2025)
Abstract: Stunting is one of the chronic nutritional problems that is still widely found in various parts of the world. Golewa Barat sub-district is one of the sub-districts located within the working area of Mangulewa Health Center. This region has a higher level of risk associated with the incidence of stunting. The purpose of the study was to determine the relationship between exclusive breastfeeding and the availability of clean water to the incidence of stunting. The research design used in this study was cross sectional. The study was conducted at the Mangulewa Health Center Working Area, West Golewa District, Ngada Regency in July 2024. The population is all mothers who have toddlers totaling 1066 respondents. The sample amounted to 73 people. The sampling technique used in this study was Simple Random Sampling. Data analysis was done univariate and bivariate. The results showed a relationship between exclusive breastfeeding (p value: 0.048) and the availability of clean water (p value: 0.002) to the incidence of stunting. It is recommended that the Puskesmas can increase public knowledge through preventive actions and health promotion to the community and conduct counseling to cadres in each village, then increase breastfeeding counseling to pregnant women, adolescents, or prospective brides.Keywords: Clean Water, Exclusive Breastfeeding, Stunting